The library’s quality management system and quality assurance in higher education: A lesson from Southeast emerging educational hub - Taib, Che Azlan; Warokka, Ari; Abdullah, Haim Hilman (IBIMA Publishing, 2012)
As one of the national vision 2020’s implementation programs, the establishment of a national Quality Assurance system focusing on the quality of the programs offered in terms of the general criteria of the structure and process of higher education is timely.In relating to the program, this paper aims to explore the efforts and other issues associated with the development and implementation of quality assurance in higher education due to its role as a service organization, which is required to enhance their quality of services.One of the important pillars determining the quality of higher-education service delivery is the library’s quality management system. By using 46 public universities’ libraries as the main sample, this study tested three hypotheses that are related to the nature of quality management practices by individual construct, as well as by aggregation value, and to what extent the difference to the numbers of staff and the type of organization will influence the quality management practices.We employed mean value and one way analysis ANOVA as the research method to solve the questions.The validity of the constructs is measured using factor analysis, and its reliability is measured by Cronbach’s alpha.Our study results revealed that the study sample perceived those constructs were important to maintain service quality to its customer.The study also informs that the number of staff and the type of organization do not influence at all on the library’s quality management system. In other words, the awareness and spirit to play an important role in achieving excellent service to its customer is the main platform over the number of staff and the type of organization.